2016
DOI: 10.3892/etm.2016.3556
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Artemisia sacrorum Ledeb. and their cytotoxic activities against human cancer cell lines

Abstract: Abstract. Flavonoids have been demonstrated to have cytotoxic activities toward numerous human cancer cells, whereas they have little or no effect on normal cells. The numerous flavonoids in traditional Chinese herbs may be promising candidates for the development of novel anti-cancer drugs. Our previous study demonstrated that CH 2 Cl 2 and 95% ethanol eluate (EE) fractions have the strongest cytotoxic activities against human cancer cell lines of the 9 fractions separated from Artemisia sacrorum Ledeb., whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…EpCAMs play an important role in cancer by possibly upregulating c-myc and cyclin A, activating the Wnt signaling pathway, and inducing proliferation [ 33 , 34 ]. Several in vivo and in vitro studies have shown that EpCAMs may act as CSC markers for many tumors, including breast, colon, liver, and pancreatic cancers [ 35 , 36 ]. In addition, high EpCAM expression levels are often correlated with poor prognoses in cancers such as breast and gallbladder cancers [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…EpCAMs play an important role in cancer by possibly upregulating c-myc and cyclin A, activating the Wnt signaling pathway, and inducing proliferation [ 33 , 34 ]. Several in vivo and in vitro studies have shown that EpCAMs may act as CSC markers for many tumors, including breast, colon, liver, and pancreatic cancers [ 35 , 36 ]. In addition, high EpCAM expression levels are often correlated with poor prognoses in cancers such as breast and gallbladder cancers [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two flavonoids obtained from the dichloromethane portion and other flavonoids from the 95% ethyl ether portions were analyzed for anticancer effects on human SK-Hep 1 hepatoma cancer cells human and HeLa cervical cancer cells. Two flavonoids have possessed significant anticancer activity against the HeLa cells line (Yuan et al 2016 ). It was found that antiproliferative properties have been ascertained for some varieties of the genus artemisia.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Finally, sixteen compounds ( 1 – 16 ), including three phenols ( 1 – 3 ), ten flavonoids ( 4 – 13 ), two triterpenoids ( 14 , 15 ), and one fatty acid ester ( 16 ), were purified ( Figure 5 ). By comparing the spectral and physicochemical properties of these compounds ( Supplementary Materials ) with those of previously reported compounds, the sixteen compounds were identified as 4-hydroxybenzoic acid ( 1 ) [ 33 ], salicylic acid ( 2 ) [ 34 ], vanillic acid ( 3 ) [ 35 ], (+)-catechin ( 4 ) [ 36 ], (–)-epicatechin ( 5 ) [ 37 ], (+)-gallocatechin ( 6 ) [ 36 ], (–)-epigallocatechin ( 7 ) [ 38 ], procyanidin B3 ( 8 ) [ 39 ], procyanidin B4 ( 9 ) [ 40 ], kaempferol ( 10 ) [ 41 ], astragalin ( 11 ) [ 42 ], trans -tiliroside ( 12 ) [ 38 ], helichrysoside ( 13 ) [ 43 ], betulinic acid-3- O - trans -caffeate ( 14 ) [ 44 ], ursolic acid-3- O - trans -caffeate ( 15 ) [ 45 ], and 1-mono(22- O -feruloyl-oxydocosanoyl)glycerol ( 16 ) [ 46 ]. Previous studies have reported the presence of various types of phytochemicals in the genus Elaeagnus , including flavonoids (e.g., rutin, epigallocatechin gallate, and isorhamnetin) and phenolic compounds (e.g., chlorogenic acid, pyrogallol, and ferulic acid) from E. umbellata [ 20 ], E. angustifolia [ 47 ], and E. pungens [ 48 ]; and triterpenoid saponins (e.g., terpengustifol), lignan glycosides (e.g., phengustifols A and B), and alkaloids (e.g., harmane and tetrahydroharmol) from E. angustifolia [ 23 , 47 ].…”
Section: Resultsmentioning
confidence: 99%